Coordination-induced emission enhancement in copper(i) iodide coordination polymers supported by 2-(alkylsulfanyl)pyrimidines. Issue 26 (16th June 2021) - Vinogradova, Katerina A.; Shekhovtsov, Nikita A.; Berezin, Alexey S.; Sukhikh, Taisiya S.; Rogovoy, Maxim I.; Artem'ev, Alexander V.; Bushuev, Mark B.
Abstract : More rigid μ2 - N, S coordination of 2-(alkylsulfanyl)pyrimidine ligands in copper(i ) iodide coordination polymers leads to a much more efficient emission in comparison with N -monodentate coordination. Abstract : First examples of copper(i ) complexes with 2-(alkylsulfanyl)pyrimidine ligands have been synthesized. Reactions of copper(i ) iodide with 2-(methylsulfanyl)pyrimidine (L 1 ) in various metal-to-ligand molar ratios in MeCN afford a ladder-type coordination polymer [Cu2 L 1 I2 ] n with polymeric chains built from double-stranded (Cu2 I2 ) n ribbons supported on both sides by μ2 - N, S -L 1 molecules. Although the second ligand, 2-(ethylsulfanyl)pyrimidine (L 2 ), differs from L 1 only by a methylene group, its reactions with copper(i ) iodide in MeCN yield not only a congenerous coordination polymer, [Cu2 L 2 I2 ] n, but also [CuL 2 I] n, in which a similar (Cu2 I2 ) n ribbon is decorated by N -monodentate L 2 molecules. Absorption spectra of all compounds represent an interplay of metal + iodine-to-ligand charge transfer (XMLCT) and ligand-centered (LC) and cluster-centered (CC) transitions, while the emission occurs from the excited states of XMLCT nature. The luminescence of [Cu2 L 1 I2 ] n and [Cu2 L 2 I2 ] n is blue-shifted and greatly enhanced in comparison with that of [CuL 2 I] n (quantum yields: 89% and 68% for [Cu2 L 1 I2 ] n and [Cu2 L 2 I2 ] n vs . 23% for [CuL 2 I] n at 77 K), which can be associated with a more rigid μ2 - N, S coordination of 2-(alkylsulfanyl)pyrimidine ligands in [Cu2 L 1 I2 ] n and [Cu2 L 2 I2 ] n leading to a less distorted T1 state.